Women in American Catholic History - Swidler, Arlene Anderson (Horizons, 1983)
Considering that History and Religious Studies are two of the areas in which feminist scholars have been most active, it is surprising how very little information is compiled in the area of American Catholic Women's History. Catholic Church historians, of course, have never found the laity of great interest, and the contemporary feminist movement has been strongly secular. Protestant and Jewish materials are more easily available, and even those books which purport to address women in American religion in general give only brief attention to Catholicisim, often by dealing solely with women in religious orders. So work on American Catholic women remains to be done.The one exception is books dealing with individual religious orders, partly because of the accessibility of the materials, though I have been gently admonished not to overestimate the order in convent archives. Studies moving wider to focus on sisters in general are still very few, and attempts to integrate these materials with lay women's history have barely begun. People interested in this field will find help in Elizabeth Kolmer, A.S.C., "Catholic Women Religious and Women's History: A Survey of the Literature," American Quarterly 30 (1978), 639-51, and in the forthcoming book by Evangeline Thomas, C.S.J., Women Religious History Sources: A Guide to Archives (New York: Bowker).